Perilaku Pencarian Informasi Mengenai Perguruan Tinggi Oleh Siswa Kelas 12 SMA Negeri 26 Jakarta - Farasabila, Tuffana; Rachman, Yeni Budi (UI Scholars Hub, 2019)
This article discusses about information seeking behavior of 12th grade students of SMA Negeri 26 Jakarta to pursue higher education. This article also discusses obstacles found during the process of information searching. This is a qualitative research with observation and interview as methods to collect data. The result shows that all informants conducted searching about higher education in the same way with what was stated by David Ellis (1993) started with starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending.